Higher GOLD spirometeric class (severity of airflow limitation) correlated with higher number of comorbidities - Bhatia, Mohit; jain, Avinash; Dixit , Shivam; Krishnan, Arya (Asian Journal of Medical Sciences, 2023)
Background: Various systemic manifestations of chronic obstructive pulmonary disease (COPD) are well known to us. One patient of COPD may have more than one associated comorbid conditions. Severity of airflow limitation is expressed as a global initiative for chronic obstructive lung disease (GOLD) spirometeric classification in patients with COPD, which has been proposed to better identify the disease severity and survival. Aims and Objectives: In this study, we aimed to find out correlation between GOLD spirometeric classification and comorbidities in patients. Materials and Methods: An observational study conducted at the Institute of Medical Science Banaras Hindu University Varanasi India. We evaluated 50 patients of COPD, containing smokers, non-smokers, and ex-smokers. The severity of airflow limitation in COPD was classified using the GOLD. The most frequent comorbidities are assessed in COPD which were cardiovascular diseases, diabetes, hypertension, osteoporosis, muscle wasting, psychological illness, and anemia. Results: Fifty patients were analyzed: Male 90%, mean age 68.5 years and mean forced vital capacity in 1 s 34.3%. There is an association between GOLD spirometeric classification and total number of comorbidities in patients. Subjects with higher GOLD spirometeric classification have more associated comorbid conditions, which suggest that these conditions may aggravate COPD course and increase risk of mortality. Conclusion: Assessment of GOLD spirometeric classification could provide information about a total number of various comorbid conditions in a patient with COPD. Patient with higher GOLD spirometeric classification has more comorbidities.